Peran Apoteker dalam Meningkatkan Penggunaan Obat Rasional di Indonesia - Rohmah, Evi Hidayatur (Maliki Interdisciplinary Journal, 2025)
Rational drug use is an essential component of healthcare systems to ensure therapeutic effectiveness, patient safety, and cost efficiency. However, irrational drug use remains a significant issue in Indonesia, as evidenced by excessive antibiotic prescribing, low patient adherence, and the prevalence of self-medication without professional supervision. Pharmacists, as healthcare professionals with expertise in medicines, play a strategic role in promoting rational drug use. This article discusses the roles of pharmacists across various healthcare settings, including hospitals, primary healthcare centers, and community pharmacies, as well as the challenges encountered in implementation. Strategies to improve rational drug use include increasing the number and distribution of pharmacists, enhancing public education, utilizing digital health technologies, and strengthening interprofessional collaboration. By optimizing the pharmacist’s role, rational drug use can be better achieved, thereby improving the overall quality of healthcare services in Indonesia.